2020
DOI: 10.1186/s12876-020-01531-5
|View full text |Cite
|
Sign up to set email alerts
|

HER2 gene assessment in liquid biopsy of gastric and esophagogastric junction cancer patients qualified for surgery

Abstract: Background Amplification of HER2 gene (ERBB2) and overexpression of HER2 protein on cancer cells are found in 10–26% of gastric cancer (GC) and esophagogastric junction cancer (EGJC). Gene copy number variation (CNV) could be detected in these patients in liquid biopsy and in cancer cells. Methods We analysed HER2 gene CNV used qPCR method in 87 sera collected from GC and EGJC patients before surgical treatment and in 40 sera obtained from healthy donors. HER2 gene CNV was also assessed in formalin-fixed para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Of interest, it has been shown that cfDNA levels in GC are more elevated than those in benign and pre-cancerous conditions, such as gastric adenomas. Based on this, a study incorporating cfDNA is underway in South Korea (NCT04665687) to identify biomarkers discriminating between neoplastic and non-neoplastic gastric lesions [30][31][32][33].…”
Section: Early Diagnosismentioning
confidence: 99%
“…Of interest, it has been shown that cfDNA levels in GC are more elevated than those in benign and pre-cancerous conditions, such as gastric adenomas. Based on this, a study incorporating cfDNA is underway in South Korea (NCT04665687) to identify biomarkers discriminating between neoplastic and non-neoplastic gastric lesions [30][31][32][33].…”
Section: Early Diagnosismentioning
confidence: 99%
“…Expanding HER2 -positivity detection methods to include liquid biopsies and next-generation sequencing could potentially provide reliable noninvasive alternatives beyond the traditional IHC and FISH testing approaches. [ 54 , 55 ] With the explosion of immunotherapy research within the last decade, one of the most exciting strategies in the future to combat HER2 + gastric or GEJ cancer is the combinatorial approach of various HER2 -targeting agents with checkpoint inhibitors, CAR-T cells, and vaccines. Through simultaneous blockade of different pathways and taking advantage of the immune system, there continues to be progress and hope in the field of advanced HER2 -positive gastric or GEJ adenocarcinoma.…”
Section: Future Directions and Considerationsmentioning
confidence: 99%
“…However, amplifications in HER2 are only present in a subset of patients with GC (approximately 20%). Amongst several other similar studies, Grenda et al detected the HER2 gene copy number at higher concentrations in the blood samples of patients with GC compared to healthy controls, with a sensitivity of 58% and a specificity of 98% ( p = 0.004) [ 45 ].…”
Section: Use Of Ctdna In Early Detection Of Gastric Cancermentioning
confidence: 99%